A Study of Transaction Cost within the Supply Chain Network in Malaysia Construction Projects - Mahanim Hanid; Othman Mohamed; Kho Mei Ye; Maznah Othman; Fadhilah Mohd Nor; Muhammad Izzad Abdul Rahman (International Journal of Supply Chain Management, 2019)
— Construction industry of Malaysia is a complex and confronts with serious issues of cost overrun. Construction supply chain which involves multi-layered supply network carries lot of potential for conflict and additional costs involving additional transaction cost. To tackle this issue, the primary aim of this study is to identify component of waste in transaction cost within multi-layered supply chain network in Malaysian construction industry. The qualitative research approach is adopted to achieve the research objectives of this study. The data were collected through semi-structured interview from five (5) quantity surveyors working with a contractor firm situated within Klang Valley region. The implication of the finding implies that the identified data are crucial in eliminating waste in transaction cost.